Trace representation of cyclotomic generator of order r. Issue 1 (2nd January 2016) - Wu, Chenhuang
ABSTRACT: The trace representation of the r -ary sequences over, which are generated by the cyclotomic generator of order r, is determined by calculating the discrete Fourier transform (DFT) when r is an odd prime or r =4. As a by-product, the linear complexity of the sequences is derived from the DFT.